2006
DOI: 10.1111/j.1083-6101.2006.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

The Contact Hypothesis Reconsidered: Interacting via the Internet

Abstract: One of the leading theories advocated for reducing intergroup conflict is the contact hypothesis. According to this theory, contact under certain conditions, such as equal status, cooperation towards a superordinate goal, and institutional support, will create a positive intergroup encounter, which, in turn, will bring about an improvement in intergroup relations. Despite its promise, the contact hypothesis appears to suffer from three major defects: (1) practicality—creating a contact situation involves overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
167
0
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(178 citation statements)
references
References 52 publications
1
167
0
10
Order By: Relevance
“…In summary, the survey results indicate that the use of SL using a project-based experiential instructional design that exploits the affordances of a 3-D virtual environment can substantially enhance the quality and experiences of student learning, as suggested by the literature (Amichai-Hamburger and McKenna, 2006;Soukup, 2004). Furthermore, our survey results support the research findings of Steinkuehler and Williams (2006) that interacting within virtual worlds can expose people to a diversity of worldviews and can help them to build a sense of community through the development of virtual social relationships.…”
Section: Project Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In summary, the survey results indicate that the use of SL using a project-based experiential instructional design that exploits the affordances of a 3-D virtual environment can substantially enhance the quality and experiences of student learning, as suggested by the literature (Amichai-Hamburger and McKenna, 2006;Soukup, 2004). Furthermore, our survey results support the research findings of Steinkuehler and Williams (2006) that interacting within virtual worlds can expose people to a diversity of worldviews and can help them to build a sense of community through the development of virtual social relationships.…”
Section: Project Resultsmentioning
confidence: 77%
“…First, studies in computer mediated communication (CMC) find that diverse people interacting via the Internet are more likely to experience positive contact and a shared understanding due to the elimination of geographical barriers, reduction in social anxiety promoting ease of disclosure, and control over the environment (Amichai-Hamburger & McKenna, 2006;Soukup, 2004). Similarly, Steinkuehler and Williams (2006) found that interacting within virtual worlds not only helps people build communities but also exposes them to a "diversity of world views" through the development of these virtual social relationships.…”
Section: Introductionmentioning
confidence: 99%
“…It might be more appropriate to consider online contact as the first stage in a process that leads to the richer intergroup contact discussed earlier. The gradual model proposed by AmichaiHamburger (2006) suggests that textonly interactions in shared online spaces can help build the trust and reciprocity needed for facetoface interactions between members of different social groups.…”
Section: New Media and Intergroup Contact Within Divided Societiesmentioning
confidence: 99%
“…Nowhere may this capacity be more critical than in the use of CMC to reduce prejudice. Scholarship addressing CMC and prejudice reduction (e.g., Amichai-Hamburger & McKenna, 2006) suggests that the Internet may foster salutary intergroup contact in small, diverse collectives by facilitating a number of conditions associated with Allport's (1954) contact hypothesis. Yet of the few implementations of CMC among Israeli sub-groups in conflict, for example, the results are contradictory (see AmichaiHamburger, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Amichai-Hamburger and McKenna (2006) have suggested that the social identification/deindividuation, or SIDE model of CMC (see for review Postmes & Baym, 2005) can explain how visually-anonymous CMC groups reduce prejudice online. Other researchers have argued that SIDE involves certain theoretical stipulations that actually prevent its useful application in intergroup reconciliation, and that the social information processing (SIP) theory and hyperpersonal model of CMC can more readily integrate with the intergroup contact hypothesis to effect prejudice reduction through extended online interactions (Walther, 2009a).…”
Section: Introductionmentioning
confidence: 99%